Perancangan Sistem Pengering Biji Kopi Hybrid Berbasis IoT Dengan Sistem Monitoring Web Real - Time - Sayid Maulana; Budi Gunawan (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to design and implement a hybrid coffee bean drying system based on the Internet of Things (IoT) with real-time web monitoring to improve the efficiency and stability of post-harvest drying. The system utilizes an ESP32 integrated with a DHT22 sensor, a moisture sensor, and a load cell to monitor environmental conditions and mass changes during drying, with data transmitted via Wi-Fi to a web dashboard with a delay of 5 seconds. The novelty of this study lies in the integration of a hybrid drying system with multi-parameter monitoring based on IoT within a single integrated platform. Experimental results show that the temperature can be maintained at 43–50 °C with a deviation of ±1.5 °C, sensor accuracy of ±0.5 °C for temperature and ±2% RH for humidity, and a load cell error of ±1–2%, with a system response time of less than 5 seconds. The drying process reduces moisture content from 55% to 12% within 18–24 hours, demonstrating that the system operates effectively, stably, and responsively in improving coffee post-harvest quality.